“THE EFFECT OF HUMAN RESOURCES INFORMATION SYSTEM ON PERFORMANCE OF THE EMPLOYMENT SECTION IN PT BIO FARMA (Persero) BANDUNG” - Rachmawati, Mariana; Permana, Indra; Kosasih, Windhayanti (CENTRAL ASIA AND THE CAUCASUS, 2022)
Human Resources Information System, is one of the factors that play an important role for quality human resources. The application of the right human resource information system is expected to determine the accuracy of the data and input sources needed to find out the information needed by the company or government agency regarding employee performance, so as to increase the effectiveness and efficiency of work for companies and government agencies. Therefore, the problem under study is to find out how far the application of human resource information systems at PT Bio Farma (Persero) Bandung is and how the level of performance of the staffing section is. Research conducted at PT Bio Farma (Persero) Bandung using descriptive methods For data collection techniques carried out by field research with interviews, questionnaires and observations in order to obtain the expected data. The results of the research on the application of the Human Resources Information System of PT Bio Farma (Persero) Bandung obtained the average value of the overall respondent's answer of 3.55 which was included in the good category because based on the interval of the average assessment criteria it could be interpreted well. Respondents' responses to PT Bio Farma (Persero) Bandung obtained an average value of 3.82 respondents' answers which are included in the good category because based on the interval of the average assessment criteria can be interpreted well because it is in the interval 3.40 - 4.19. The conclusion of this study is the magnitude of the influence of Human Resource Information Systems on the Performance of PT Bio Farma (Persero) Bandung of 0.656. This means that there is a strong relationship between Human Resources information systems and employee performance.